1278. Comparing Rates of Routine HIV and HCV Screening to Estimate the Impact of Consent on Identifying Patients With Undiagnosed HIV. (26th November 2018) - Tlamsa, Aileen; Heo, Moonseong; Thompson, Devin; Moir, Lorlette; Shukla, Shuchin; Weiss, Jeffrey; Litwin, Alain; Felsen, Uriel
Abstract: Background: HIV and HCV are both treatable viruses for which routine screening among specific age cohorts is recommended. New York State requires patient consent prior to screening for HIV but not HCV. To estimate the impact of the consent requirement, we compared rates of HIV and HCV screening. Methods: We performed a retrospective study of all adult patients admitted to a tertiary-care hospital in the Bronx, NY, between April 2015 and June 2016. During the study period, automated prompts in the electronic medical record facilitated screening for HIV among patients ages 21–64, and for HCV among patients born between1945-1965. We compared the proportions of patients qualifying for screening for HIV, HCV, or both who were appropriately screened prior to discharge to calculate an adjusted risk difference between performance of HIV and HCV screening. Using the local prevalence of undiagnosed HIV, we estimated the number of missed HIV diagnoses attributable to the difference in screening rates. Results: A total of 21, 413 unique hospitalized patients ages 21–64 and/or born between 1945–1965 were analyzed. Among those qualifying for screening for HIV alone or HCV alone, 39.7% and 58.6% were screened prior to discharge, respectively. Among those qualifying for both HIV and HCV screening, 6.7% were screened for HIV alone, 29.3% were screened for HCV alone, and 30.3% were screened for both. The risk difference between HCV and HIV screening adjusted for patient and admission characteristics was 22.0% (95% CI 20.6%-23.4%). Using an estimated prevalence of undiagnosed HIV of 0.2%, this risk difference corresponds to approximately four (95% CI 3.6–4.1) missed cases of HIV during the study period. Conclusion: There was a large difference in the number of patients appropriately screened for HIV compared with HCV. While the requirement for consent was the only operational difference in performing routine screening for HIV compared with HCV, differences in how the two viruses are perceived may also have contributed to the observed difference in screening rates. Nevertheless, our findings suggest that removing the requirement for consent prior to HIV screening may increase the number of cases of previously undiagnosed HIV identified by routine screening. Disclosures: All authors: No reported disclosures.